The Implementation of Roland Barthes semiotics in Al-Baqarah Verse 143 on the Word of Ummatan Wasathan: Penerapan Semiotika Roland Barthes dalam Surat Al-Baqarah Ayat 143 pada Kata Ummatan Wasathan (Takwil: Journal of Quran and Hadith Studies, 2024)
Umatan wasathan is a way of forming the character of Muslims which represents various differences in beliefs between religions. Umatan wasathan has an important role in maintaining harmony, peace and tranquility so that a harmonious society can be created amidst differences. In the process of its implementation, the Umatan wasathan makes Muslims not to be excessive, to be in a middle position, not extreme right or left, but to have a moderate character that adorns the personality of every Muslim. This research discusses the Umatan wasathan in the Al-Qur'an surah al-Baqarah verse 143. This research uses a qualitative research type of literature study which is presented descriptively-analytically using Roland Barthes' semiotic approach. The results of the research show that the Wasathan Ummah is a people who have a moderate character which is reflected in the ability to act fairly, be balanced, and be able to implement beneficial values. Muslims are asked to be able to combine two things, namely, piety in the afterlife and worldly life. This research recommends that future researchers examine the future of Indonesian life amidst diversity and religiousity.